The third harmonic current contribution during three-phase to ground fault - Riman, N.I.S. (Institute of Electrical and Electronics Engineers Inc., 2017)
In recent times, the Gas District Cooling (GDC) plant in Universiti Teknologi PETRONAS (UTP) has suffered faults throughout the power system network due to many reasons. It was reported that third harmonic component exists in its fault current. Synchronous generator is one of the triplen harmonic sources and third harmonic is the major component. Therefore, this paper intends to study the contribution of third harmonic produced by synchronous generator during three-phase to ground fault. Lab scale experiments are conducted to investigate the contribution of third harmonic towards overall fault current. The third harmonic current during normal operation is first measured and considered as base data. Then, third harmonic current during three-phase to ground fault is measured and compared with the base data. During three-phase to ground fault, the load impedance is removed from the circuit and the line is connected directly to the ground. It is found out that the contribution of third harmonic during three-phase to ground fault is significantly high compared to normal operation. The third harmonic fault current depends on effective zero sequence impedance of the circuit. During the fault, the effective zero sequence impedance of the circuit reduces and inversely the third harmonic current increases greatly. © 2016 IEEE.